Budaya Kewirausahaan pada UMKM Kerupuk Karak (Studi Kasus pada UMKM Kerupuk Karak Dusun Gempol, Desa Tawangsari, Kecamatan Teras, Kabupaten Boyolali) - Yuliana Rohmawati; Sudharto Prawoto Hadi (Universitas Diponegoro, 2017)
Small and medium enterprises grow in the community, and require special attention in order to maintain sustainability. The number small and medium enterprises in Indonesia is currently only of 1.56 percent from 4 percent the ideal number according to the World Bank. To meet the Word Bank standard, the entrepreneurial culture needs to develop.This research was conducted in Gempol, Tawangsari, Teras, Boyolali Regency. This research aims to identify the aspects that influence the culture of entrepreneurship in small and medium enterprise as well as the enterprise competitiveness. The data collection techniques are in-depth interviews, observation participation with UMKM owner, employees and staff of the Office of Cooperatives and Small Medium Enterprise Boyolali Regency. Data was analysed with description, interpretation and explanation. The results of the analysis are compared with theories from Bygrave (1994:5) in Alma (2011:57) concept of 10 D and Sukhemi and Maisaroh (2011:27) in the development of a culture of entrepreneurship are; the ability of residentsin looking at opportunities, the availability of the facilities, talent and creativity of citizens is high, the ability of citizens to learn and try out very strong, and there is a consciousness and a willingness for cooperation or collaboration. Of these stages found 1) ability to see opportunities, with 3 supporting indicators; 2) facilities and the environment, with 2 supporting indicators; 3) talent and creativity, with 3 supporting indicators; 4) study skills and tries, with 3 supporting indicators; 5) awareness and willingness to cooperate. The conclusion are the most supportive factor is product innovation. The recommendations follow: 1) it is required for UMKM owner to looking at opportunities that exist so that it can be utilized to enhance the competitiveness of businessmen; 2) it is required additional training facilities to match the needs of businessmen and required the addition of a number of quotas for training. In addition it is required to provide training that is relevant to the specific form of UMKM.